2013
DOI: 10.1167/iovs.12-10552
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Thickness Measurements of Macular Inner Retinal Layers Using SD-OCT With or Without Correction of Ocular Rotation

Abstract: Citation: Hirasawa H, Araie M, Tomidokoro A, et al. Reproducibility of thickness measurements of macular inner retinal layers using SD-OCT with or without correction of ocular rotation. Invest Ophthalmol Vis Sci. 2013;54:256254: -257054: . DOI:10.1167 PURPOSE. To evaluate the intervisit reproducibility of spectral-domain optical coherence tomography (SD-OCT) measurement of the macular retinal nerve fiber layer thickness (mRNFLT); combined ganglion cell layer and inner plexiform layer (GCLþIPL) thickness; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Our intersession results were as excellent as in previous studies [2,9,10]. However, none of these studies had assessed interobserver intrasession reproducibility, which may be of some interest when comparing clinical trials data.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our intersession results were as excellent as in previous studies [2,9,10]. However, none of these studies had assessed interobserver intrasession reproducibility, which may be of some interest when comparing clinical trials data.…”
Section: Discussionsupporting
confidence: 77%
“…In a recent study [10] assessing the reproducibility of thickness measurements of macular inner retinal layers using SD-OCT with or without correction of ocular rotation, an SD-OCT device (3D OCT-1000, version 2.13; Topcon, Inc.) was used to evaluate the intervisit reproducibility of several parameters, including GC-IPL, using the CV, reproducibility coefficient and ICC. The authors reported better and excellent reproducibility of the macular GC-IPL and GCC thickness compared with that of the RNFL measurement in the macular and circumpapillary areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, small amounts of changes in physiological ocular rotation exist among each test session, which may affect the intertest measurement reproducibility of peripapillary RNFL thicknesses. 27 Therefore, in this study, we compensated for the potential effect of the ocular rotation on the disc-foveal angle by using fundus photographs overlaid on spectral-domain (SD)-OCT images (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Most authors consider that methods with a COV less than 10% have high reproducibility, while a COV less than 5% indicates very high reproducibility 13. To assess the reliability of the repeated measurements, the intraclass correlation coefficients for absolute agreement was calculated.…”
Section: Methodsmentioning
confidence: 99%